2019
DOI: 10.1029/2018jd029961
|View full text |Cite
|
Sign up to set email alerts
|

Weakening of the Teleconnection From El Niño–Southern Oscillation to the Arctic Stratosphere Over the Past Few Decades: What Can Be Learned From Subseasonal Forecast Models?

Abstract: While a connection between the El Niño–Southern Oscillation (ENSO) and the Northern Hemisphere wintertime stratospheric polar vortex appears robust in observational studies focusing on the period before 1979 and in many modeling studies, this connection is not evident over the past few decades. In this study, the factors that have led to the disappearance of the ENSO‐vortex relationship are assessed by comparing this relationship in observational data and in operational subseasonal forecasting models over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 79 publications
(147 reference statements)
6
28
0
Order By: Relevance
“…4c and d. Specifically, ozone anomalies are usually accompanied by anomalies in the Arctic vortex ( Fig. 4a and b), and previous work has shown that spring Arctic vortex anomalies independent of ozone can influence surface conditions (Black and McDaniel, 2007;Ayarzagüena and Serrano, 2009;Hardiman et al, 2011). We now demonstrate that vortex anomalies are associated with polar cap PS anomalies in the CCMI models as well and then try to isolate statistically the relative importance of ASO.…”
Section: Effect Of Arctic Stratospheric Ozone (Aso) On Polar Surface supporting
confidence: 63%
“…4c and d. Specifically, ozone anomalies are usually accompanied by anomalies in the Arctic vortex ( Fig. 4a and b), and previous work has shown that spring Arctic vortex anomalies independent of ozone can influence surface conditions (Black and McDaniel, 2007;Ayarzagüena and Serrano, 2009;Hardiman et al, 2011). We now demonstrate that vortex anomalies are associated with polar cap PS anomalies in the CCMI models as well and then try to isolate statistically the relative importance of ASO.…”
Section: Effect Of Arctic Stratospheric Ozone (Aso) On Polar Surface supporting
confidence: 63%
“…This brief analysis suggests some relationship, but given the short record, it is not clear whether this interannual relationship might be dominated by ENSO teleconnections to the stratosphere (Domeisen et al, ) or is a sampling artifact. Note that during the 1981–2016 period, more SSWs occurred during La Niña than El Niño (Garfinkel et al, ). Of the nine El Niño winters that were followed by early FWs, only two had midwinter SSWs.…”
Section: Resultsmentioning
confidence: 99%
“…The fully coupled approach of Calvo et al (2015) allows consistency between the evolving ozone distributions and dynamical conditions among other differences in the model configuration, which may explain the differences between their conclusions and those of studies prescribing ozone concentrations. However, there is some ambiguity in the approach of Calvo et al (2015) as to whether the surface anomalies are due exclusively to chemical depletion of ozone: ozone anomalies are usually accompanied by anomalies in the Arctic vortex (i.e., early or delayed breakup of the Arctic vortex for high ozone or low ozone respectively, Hurwitz et al, 2011), and vortex anomalies independent of ozone have been shown to influence surface conditions (Black and McDaniel, 2007;Ayarzagüena and Serrano, 2009;Hardiman et al, 2011). Hence the degree to which the surface anomalies found by Calvo et al (2015) are related to chemical ozone depletion rather than the altered dynamical state of the vortex which also affects ozone concentrations is ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…The standard deviation in CHASER is much less than that observed, and hence this model was excluded from further analysis. et al (2017) (e.g., Black and McDaniel, 2007;Ayarzagüena and Serrano, 2009;Hardiman et al, 2011), and it is not clear whether the surface response is due to the dynamical impact from the final warming as opposed to the radiative impact of the ozone anomaly that typically accompanies a final warming. Finally, Xie et al (2016) suggest that ASO anomalies influence sea level pressure anomalies over the North Pacific, which in turn modulates subtropical sea surface temperatures.…”
Section: Introductionmentioning
confidence: 99%